Characterization of tonoplast pyrophosphatase from Hevea brasiliensis latex - Siswanto; Clement A; Jacob J L; Prevot J C (Indian Journal of Natural Rubber Research, 1994)
A pyrophosphatase (PPase) is evidenced on the lutoidic membrane in Hevea brasiliensis latex. Presence of Mg2+ is needed during the membrane washing, to preserve the tonoplastic enzyme activity. PPase functioning is Mg2+ and pyrophosphate (PPi)Km are measured. The substrate affinity is high (50uM). It is relatively thermosensitive. Many products were tested on the PPase functioning. K+ is a strong activator. It increases the reaction activity but does not modify the enzyme affinity. Among the monovalent cations, only Rb+ has a similar efffect. No divalent cation can take the place of Mg2+, but some of them such as Ca2+ or Mn2+ are inhibitors. Inhibition induced by cysteine, pCMB and NEM indicates the importance of SH groups in the enzyme active site. DIDS which breaks anion transport, inhibits the enzyme. DCCD and NaNO3, inhibitors of lutoidic ATPase, have no effect on the lutoidic PPase. Taking the results into account, it is possible to compare latex tonoplastic and cystolic PPases. The physiological role of this tonoplastic PPase is discussed.
Keywords: Hevea brasiliensis; Latex; Lutoid; Pyrophosphatase; Rubber synthesis; Tonoplast